Mechanical Analysis of Burke-Shaw Chaotic System - Shukla, Vijay K.; Pandey, Arun K.; Acharya, Saraswati; Kumar, Abhishek; Tripathi, Neeraj K.; Mishra, Prashant K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, the mechanic analysis of Burke-Shaw system have been studied. Firstly, the system is transformed into Kolmogorov type system and further decomposed into four types of torques: inertial torque, internal torque, dissipation torque and external torque. Five scenarios are examined using combinations of various torques in order to identify the key elements for chaos creation and their physical significance. In these scenarios, the conversion between kinetic energy, potential energy and Hamiltonian energy are examined. The interaction between energy and the parameters is also explored. The conclusion reveals that any combination of three forms of torques can not create chaos in Burke-Shaw system but a combination of four types of torques concrete it.